A SWARM Based Approach in Saving Flood Survivors - Chowdhury, Dilip Roy; Bose, Subhajit (International Journal of Computer Sciences and Engineering, 2015)
Swarm intelligence (SI) is a branch of artificial intelligence that has evolved based on the collective behavior of social insect colonies and other animal societies that have decentralized mode of work control. It is the collective behaviour (intelligence) exhibited by many individual elements for carrying out a common work that coordinate among them using a decentralized control and self-organization both in natural and artificial system. This paper proposes an optimized algorithm based on swarm intelligence algorithms to save people who are stuck in flood in the minimum time when the number of motorized inflatable rescue boats available is comparatively less to the number of people stuck in flood.